Social support and common mental disorder among medical students - Adriano Gonçalves Silva; Ana Teresa de Abreu Ramos Cerqueira; Maria Cristina Pereira Lima (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: Different kinds of psychological distress have been identified for students in the health field, especially in the medical school. OBJECTIVE: To estimate the prevalence of mental suffering among medical students in the Southeastern Brazil and asses its association with social support. METHODS: It is a cross-sectional study. Structured questionnaires were applied for students from the 1st up to the 6th years of the medical school of Universidade Estadual Paulista "Júlio de Mesquita Filho", assessing demographic variables related to aspects of graduation and adaptation to the city. Psychological suffering was defined as a common mental disorder (CMD) assessed by the Self Reporting Questionnaire (SRQ-20). Social support was assessed by the social support scale of the Medical Outcomes Study (MOS). The association between the outcome and explanatory variables was assessed by the χ2 test and Logistic Regression, for the multivariate analyses, using p < 0.05. RESULTS: The response rate was of 80.7%, with no differences between sample and the population regarding gender (p = 0.78). The average age was 22 years old (standard deviation - SD = 2.2), mainly women (58.2%) and students who were living with friends (62%). The prevalence of CMD was 44.9% (95%CI 40.2 - 49.6). After the multivariate analyses, the explanatory variables that were associated with CMD were: feeling rejected in the past year (p < 0.001), thinking about leaving medical school (p < 0.001) and "interaction" in the MOS scale (p = 0.002). CONCLUSIONS: The prevalence of CMD among medical students was high and insufficient social support was an important risk factor. Our findings suggest that interventions to improve social interaction among those students could be beneficial, decreasing the prevalence of CMD in this group.